Use of ixekizumab in an HIV-positive patient with psoriatic arthritis. (April 2022) - Qian, Feng; Yan, Yujuan; Huang, Jinlong; Xu, Weilu; Zhu, Yueping; Liu, Jin; Wu, Xuehua; Chen, Fan
Psoriasis is a chronic immune-mediated disease of the skin. The incidence of psoriasis among people living with HIV (PLHIV) is higher than that in the general population. The mechanism is complex, the manifestations are varied, and the treatment is difficult. Biotherapy has greatly alleviated psoriasis, but clinical trials often exclude PLHIV, and evidence is limited to case reports. Here, we report a man living with psoriatic arthritis who had poor response to traditional treatments. After receiving the anti-interleukin (IL)-17 monoclonal antibody (ixekizumab), the arthritis symptoms were significantly relieved, while CD4 + T cell count increased and the viral load of HIV-1 remained undetectable in combination with antiretroviral therapy (ART). In conclusion, anti-IL-17 monoclonal antibody is a promising and safe treatment for psoriatic arthritis in HIV-positive patients.